Analisis Fraud Hexagon dalam Mendeteksi Fraudulent Financial Reporting pada Perusahaan Jasa Kesehatan yang Terdaftar di BEI Tahun 2018-2022 - Anggi Ria Prasasti; Hexana Sri Lastanti (Jurnal Syntax Admiration, 2024)
This study aims to determine whether pressure affects fraudulent financial reporting. By using quantitative methods for health service companies listed on the Indonesia Stock Exchange in 2018-2022. The study used secondary data, namely the company's annual financial statements and sampling techniques carried out by the purphose sampling method. Descriptive is used to see Hexagon's Fraud Analysis in detecting Fraudulent Financial Reporting with the Audit Committee as moderating (Empirical Study on Health Services Listed on the Indonesia Stock Exchange for the 2018-2022 Period). This study used 3 variables, namely independent variables, dependent variables and moderation variables. Based on the testing conducted and the results of the research discussion, it can be concluded that: 1) Stimulus affects financial statement fraud. 2) Opportunities do not positively affect financial statement fraud. 3) Rationalization has a positive effect on financial statement fraud.